2015
DOI: 10.1007/s10856-015-5590-4
|View full text |Cite
|
Sign up to set email alerts
|

Porous biphasic calcium phosphate ceramics coated with nano-hydroxyapatite and seeded with mesenchymal stem cells for reconstruction of radius segmental defects in rabbits

Abstract: The osteoconduction of porous biphasic calcium phosphate (BCP) ceramics has been widely reported. In a previous study, we demonstrated that applying a nano-hydroxyapatite (nHA) coating enhances the osteoinductive potential of BCP ceramics, making these scaffolds more suitable for bone tissue engineering applications. The aim of the present study was to determine the effects of reconstructing radius defects in rabbits using nHA-coated BCP ceramics seeded with mesenchymal stem cells (MSCs) and to compare the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…1, 2, 3, 4 Among various Ca-P ceramics, porous biphasic calcium phosphate ceramics (BCP) have attracted much attention in the reconstruction of large and complex bone defects because of their excellent osteoconduction and proper degradation. 5, 6, 7 However, a rather long duration of the bone consolidation phase is typically required after therapy using BCP, which may elicit unexpected complications and inconvenience care clinics.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2, 3, 4 Among various Ca-P ceramics, porous biphasic calcium phosphate ceramics (BCP) have attracted much attention in the reconstruction of large and complex bone defects because of their excellent osteoconduction and proper degradation. 5, 6, 7 However, a rather long duration of the bone consolidation phase is typically required after therapy using BCP, which may elicit unexpected complications and inconvenience care clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that calcium phosphate appears to have the advantages of good osteoconductivity and has been investigated in the clinical treatment of rabbits, 65,66 dogs 11,62,67,68 and rats, 69,70 Yu et al 62 implanted CaP ceramics with interconnected channels into the defect sites of rats; the results indicated that the in-growth of blood vessels was observed in the border of the scaffold. nHA-coated BCP ceramics seeded with mesenchymal stem cells (MSCs) were prepared and shown to enhance the formation of new bone tissue in the BCP ceramics after being implanted into rabbits for 12 weeks.…”
Section: Biological Properties Of Calcium Phosphate Biomaterialsmentioning
confidence: 99%
“…Hu J et al [18] analyzed the morphology response of nano-hydroxyapatite particles in relation to bone formation. They obtained as results that nano-hydroxyapatite favored cell adhesion and promoted osteogenic differentiation, as evidenced by the up-regulated expression of osteogenic genes, increasing alkaline phosphatase activity and increasing osteopontin production.…”
Section: Discussionmentioning
confidence: 99%